Stress-induced senescence and plant tolerance to abiotic stress. (26th July 2017) - Sade, Nir; del Mar Rubio-Wilhelmi, María; Umnajkitikorn, Kamolchanok; Blumwald, Eduardo
Abstract : Abiotic stresses accelerate plant senescence, leading to losses in photosynthesis and reduced yields. It may be possible to enhance stress tolerance by altering sink–source relationships within the plant. Abstract: Senescence is an age-dependent process, ultimately leading to plant death, that in annual crop plants overlaps with the reproductive stage of development. Research on the molecular and biochemical mechanisms of leaf senescence has revealed a multi-layered regulatory network operating to control age-dependent processes. Abiotic stress-induced senescence challenges source–sink relationships and results in significant reduction in crop yields. Although processes associated with plant senescence are well studied, the mechanisms regulating stress-induced senescence are not well known. Here, we discuss the effects of abiotic stress on crop productivity, mechanisms associated with stress-induced senescence, and the possible use of these mechanisms for the generation of plant stress tolerance. We emphasize the involvement of source strength and stability of the photosynthetic apparatus in this process, and suggest a possible role of a perennial plant life strategy for the amelioration of stress-induced senescence.